2019
DOI: 10.1007/s10157-019-01818-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of dotinurad, a novel selective urate reabsorption inhibitor, in Japanese hyperuricemic patients with or without gout: randomized, multicenter, double-blind, placebo-controlled, parallel-group, confirmatory phase 2 study

Abstract: Background Dotinurad, a novel selective urate reabsorption inhibitor (SURI), reduces serum uric acid levels by selectively inhibiting urate transporter 1 (URAT1) for the treatment of hyperuricemia with or without gout. We confirmed the serum uric acid lowering effect and safety of dotinurad. Methods This was a confirmatory, 12-week, randomized, multicenter, double-blind, placebo-controlled, parallel-group, dose escalation, late phase 2 study. The study arms were dotinurad 0.5, 1, 2, or 4 mg and placebo. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…After removing duplicates and screening titles and abstracts, 30 full-text articles were reviewed. Finally, four RCTs (684 patients) were eligible for inclusion in the study (Figure 1) [2,7,8,10]. All the included studies assessed the efficacy and safety of dotinurad in hyperuricemic patients with or without gout.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After removing duplicates and screening titles and abstracts, 30 full-text articles were reviewed. Finally, four RCTs (684 patients) were eligible for inclusion in the study (Figure 1) [2,7,8,10]. All the included studies assessed the efficacy and safety of dotinurad in hyperuricemic patients with or without gout.…”
Section: Resultsmentioning
confidence: 99%
“…All the included studies assessed the efficacy and safety of dotinurad in hyperuricemic patients with or without gout. Two trials compared dotinurad with placebo, while the rest of the two used active control, i.e, benzbromarone and febuxostat as a comparator [2,7,8,10].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Completed phase 2 studies of dotinurad demonstrated a potent uric acid lowering effect as well as a favorable safety profile [10,11]. In a phase 1 study in healthy adults, PK parameters of dotinurad showed a linear C max and its time to C max (T max ) and elimination half-life (T 1/2 ) were approximately 3 and 10 h, respectively, which were nearly constant irrespective of the dose level.…”
Section: Introductionmentioning
confidence: 99%